2017
DOI: 10.1159/000486115
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Influence on Oxidative Stress and Cardiac Remodeling in Rats During Transition from Compensated Left Ventricular Hypertrophy to Heart Failure

Abstract: Background/Aims: To evaluate the effects of the antioxidant N-acetylcysteine (NAC) on cardiac structure and function in rats with long-term ascending aortic stenosis (AS). Methods: Four months after inducing AS, Wistar rats were assigned into the groups Sham, AS, and AS treated with NAC (AS-NAC) and followed for eight weeks. Cardiac structure and function were evaluated by echocardiogram. Myocardial antioxidant enzymes activity was measured by spectrophotometry and malondialdehyde serum concentration by HPLC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Since mitogen‐activated protein kinases (MAPK) may be involved in myocardial response to oxidative stress, we also evaluated their proteins expression in myocardium. Results for myocardial morphometric evaluation, oxidative stress analyses and protein expression from Sham and AS rats have been previously published …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since mitogen‐activated protein kinases (MAPK) may be involved in myocardial response to oxidative stress, we also evaluated their proteins expression in myocardium. Results for myocardial morphometric evaluation, oxidative stress analyses and protein expression from Sham and AS rats have been previously published …”
Section: Introductionmentioning
confidence: 99%
“…Results for myocardial morphometric evaluation, oxidative stress analyses and protein expression from Sham and AS rats have been previously published. 27…”
mentioning
confidence: 99%
“…cytochrome c oxidase subunit I) [161,305]Platelet-derivedgrowth factor receptor beta [272]Carnosine [283,286,288]Serine/threonine-protein kinase STK11 [309]Glutathione [260]Ether-a-go-go-related channels [310]Lipid peroxidation-derived aldehydesMDA Free MDA : Spectrophotometric methods (sample derivatization with TBA) [170,[172], [173], [174]] MDA-protein adducts : Spectrophotometric methods (sample derivatization with TBA, strong acids, hydrazine-based or non-hydrazine-based reagents) [171,180,183] LC-UV or LC-FD [176,177,180] LC-MS/MS (e.g. SRM/MRM MS or label-free ; sample derivatization with AIDA assay, 4-APC) [[186], [187], [188],194,195] GC-MS/MS (sample derivatization with hydrazine-based or non-hydrazine-based reagents) [178,179,190,191,196] CE-UV [193]Atherosclerosis [112]Coronary and peripheral artery disease [196,311]Aortic stenosis [265]Heart failure [312]Apolipoprotein B-100 (LDLs) [43]Apolipoprotein AI (HDLs) [313]Mitochondrial proteins [314]Carnosine [282,285]Lipid peroxidation-derived aldehydesACR Free ACR : Fluorescence methods (e.g. Skraup reaction with m-aminophenol, lanthanide probe) [202,204,205]LC-FD [206,208]LC-MS/MS (sample derivatization) [214] ACR-protein adducts : Immunochemical methods [209,…”
Section: Methods For Identification and Quantitation Of Lipid Peroxidmentioning
confidence: 99%
“…Indeed, a recent systematic review highlighted the ameliorative properties of NAC in preventing diabetes-induced cardiac damage through inhibition of oxidative stress [264], together with several preclinical studies supporting this effect. Reyes et al demonstrated in a rat model of long-term ascending aortic stenosis NAC treatment resulted in a reduction of myocardial fibrosis during the transition from compensated left ventricular (LV) hypertrophy to heart failure, paralleled by reduced oxidative stress due to restored glutathione levels and reduced MDA [265]. Giam et al demonstrated that NAC could blunt cardiac fibrosis and related remodeling in the setting of heart failure, in mice with cardiomyopathy secondary to the cardiac-specific overexpression of mammalian sterile 20‐like kinase 1, and this effect was ascribed to reduced oxidative stress [266].…”
Section: Molecular Strategies To Prevent Ales Formation In the Cardiomentioning
confidence: 99%
“…Hematoxylin and eosin-stained slides from LV tissue were used to measure approximately 50 cardiomyocyte diameters as the lower distance between myocyte borders drawn across the nucleus [2426].…”
Section: Methodsmentioning
confidence: 99%